Orientation of Cultural Values in West Java Folklore “Si Buncir”: Cultural Representation Study - Apriliyani, N. Yeffa Afnita; Sunendar, Dadang; Syihabuddin, Syihabuddin; Sumiyadi, Sumiyadi (Faculty of Humanities, Universitas Jenderal Soedirman, 2023)
A cultural approach in folklore can be both a medium and an effective learning material. Culture contained various kinds of values that were needed as a provision for the lives of students later. This study examined the orientation of cultural values contained in the folklore